2016
DOI: 10.1088/0957-4484/27/8/085604
|View full text |Cite
|
Sign up to set email alerts
|

Substrate control for large area continuous films of monolayer MoS2by atmospheric pressure chemical vapor deposition

Abstract: Growing monolayer MoS2 films that are continuous with large domain sizes by chemical vapor deposition is one of the major challenges in 2D materials research at the moment. Here, we explore how atmospheric pressure CVD can be used to grow centimeter scale continuous films of monolayer MoS2 films directly on Si substrates with an oxide layer whilst also obtaining large domain sizes exceeding 20 μm within the films. This is achieved by orientating the growth substrate in a vertical position to improve the unifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 31 publications
4
71
0
Order By: Relevance
“…As a result, clean monolayer crystals tend to grow only in a specific area where the MoO 3 vapor concentration is relatively low (e.g., at the sides of the substrates) . For this reason, there have been many alternative attempts to control the nucleation density by placing the growth substrate away from the precursor, or adjusting the oxygen flow, argon flow, growth temperature, and the furnace position during the growth process . However, these have all resulted in a nonuniform and position‐dependent crystal quality, a relatively small crystal size, low coverage, or a contaminated film.…”
mentioning
confidence: 99%
“…As a result, clean monolayer crystals tend to grow only in a specific area where the MoO 3 vapor concentration is relatively low (e.g., at the sides of the substrates) . For this reason, there have been many alternative attempts to control the nucleation density by placing the growth substrate away from the precursor, or adjusting the oxygen flow, argon flow, growth temperature, and the furnace position during the growth process . However, these have all resulted in a nonuniform and position‐dependent crystal quality, a relatively small crystal size, low coverage, or a contaminated film.…”
mentioning
confidence: 99%
“…On the other hand, the color of the sample after sulfurization process is relatively different with the one of Mo/SiO 2 /Si substrate. It was changed from violet color to dark blue color, which is similar with the color of thin layer MoS 2 grown by CVD method [12][13][14]. Fig.…”
Section: Methodsmentioning
confidence: 59%
“…So, special attention has been given to CVD as it has a greater possibility to grow large area high-quality uniform mono-and few-layer MoS2 with low manufacturing costs [20][21][22]. CVD growth of MoS2 could be achieved by different Mo source materials such as molybdenum trioxide (MoO3) powder [19,[23][24][25], Mo film [26], ammonium heptamolybdate [21,27], gas source of Mo(CO)6 [20,23,27], and MoCl5 [20,23]. Zhan et al [28] reported the growth of MoS2 film on silicon dioxide (SiO2) substrate by sulfurization of Mo metal film in a two-step CVD process but this approach resulted in a lack of crystallinity and poor electrical properties of MoS2 films [29].…”
Section: Introductionmentioning
confidence: 99%